The Features of Decay Kinetics of Photovoltage in Silicon Crystals Used in Solar Energy Caused by Weak Stationary Magnetic Field - L.P. Steblenko; O.A. Korotchenkov; A.A. Podolyan; D.V. Kalinichenko; A.N. Kuryliuk; Yu.L. Kobzar; A.N. Krit; S.N. Naumenko (Журнал нано- та електронної фізики)
The influence of a weak stationary magnetic field on the decay kinetics of photovoltage in solar-Si crystals is studied. The features in the behavior of electrophysical parameters showed that the stability of the short-term and long-term components of photovoltage depends on the duration of magnetic treatment. Short time of magnetic treatment leads to increase, and long magnetic treatment causes reduction both components of photovoltage in comparison with control crystals. It is revealed that character of magnitostimulated change of photovoltage kinetics correlates with a charge condition of surface.